القيم التنظمية و أثرها على الأداء الوظيفي دراسة ميدانية في مؤسسة سونلغاز بالأغواط - غالم أحمد; غربي عبد النور; بن عيسى الأزهاري (My University, 2023)
This study aims to examine the impact of organizational values on job performance in Sonelgaz Company in Laghouat, by answering the following questions: - Does participation in decision-making affect job performance in Sonelgaz Company in Laghouat? - Does fairness affect the job performance of workers in Sonelgaz Company in Laghouat? We sought to answer these questions using a descriptive approach, utilizing a questionnaire distributed to a random sample of employees in Sonelgaz Company in Laghouat. After conducting the methodological and field procedures of the study, we extracted the following results: - There is an effect of fairness on the job performance of workers in Sonelgaz Company in Laghouat. - There is an effect of participation in decision-making on job performance in Sonelgaz Company in Laghouat. Keywords: organizational values, participation in decision-making, fairness, job performance, Sonelgaz Company